A Study of Energy Efficiency And Thermal Performance of A Smart Shoe Drying System In Supporting Green Technology Applications - Rosly, Nur Rafiqah; Shuib, Siti Khalijah; Ibrahim, Mohamad Shahril; Kosnan, Noor Mayafaraniza (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: The purpose of this study is to understand the energy efficiency and thermal characteristics of using Positive Temperature Coefficient (PTC) heaters in a smart shoe drying system, to support the development of sustainable and energy-efficient Green Technology innovations. Background Problems: Current shoe-drying methods are inefficient and problematic. Air-drying is slow, while using hair dryers or heaters wastes energy and risks damage due to overheating and lack of temperature control. While a new smart dryer with a PTC heater has been designed to solve this, its actual energy efficiency and thermal performance remain unstudied. Without examining its electricity use, how shoe type affects drying, and how well it converts energy to evaporate moisture, it’s unclear if this system is truly an effective and sustainable green technology. Research Methods: The smart shoe drying system was tested using three shoe types (sports shoes, casual shoes, and safety boots) at a controlled operating temperature of 45°C (±0.5°C) with a 240V AC power supply. Drying time was measured with a digital stopwatch, energy consumption with a multi-meter, and water mass by weighing the shoes before and after wetting. Finding/Results: Sports shoes dried the fastest (24 minutes) and had the highest energy efficiency at 50.2%. Safety boots and casual shoes showed lower efficiencies of 33.7% and 29.7%, respectively. Energy consumption per drying cycle ranged from 0.874 to 1.674 kWh, classifying the system below the moderate consumption range. The PTC heater’s self-limiting temperature feature ensured stable operation without additional thermal controls, minimizing overheating risks and energy loss. The 3D-printed drying chamber effectively promoted rapid evaporation and maintained safety. Conclusion: This smart shoe drying system qualifies as a small-scale green electrical appliance with significant potential. Future upgrades integrating solar energy and IoT optimization could position it as a class A+ energy-saving device within domestic sustainable development frameworks.